2014
DOI: 10.1159/000357358
|View full text |Cite
|
Sign up to set email alerts
|

Improved Efficacy of Endobronchial Ultrasound-Guided Fine-Needle Aspiration Biopsy in Comparison to Endobronchial Ultrasound-Guided Miniforceps Biopsy

Abstract: Objective: Endobronchial ultrasound-guided fine-needle aspiration (EBUS-FNA) cytology and EBUS-miniforceps biopsy (MFB) have emerged as less invasive tools for evaluating mediastinal lymph nodes and pulmonary lesions. The aim of this study is to compare the diagnostic yields of EBUS-FNA cytology to EBUS-MFB. Study Design: A retrospective cohort study was performed by reviewing the database at our institution between December 12, 2010, and August 10, 2012. A total of 476 consecutive cases were identified. Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Techniques to obtain cytologic material include induced sputum, bronchial brushings, bronchial washings, percutaneous fine‐needle aspiration (FNA), conventional transbronchial FNA, and endobronchial ultrasound guided FNA . Each technique has characteristic sensitivities and specificities with recent studies suggesting that image guided FNA has the best diagnostic accuracy . Given the importance of these sampling techniques, it is clear that cytopathologists play a central role in the diagnostic evaluation of pulmonary nodules and masses.…”
Section: Proposed Pulmonary Cytology Specimen Terminology and Classifmentioning
confidence: 99%
“…Techniques to obtain cytologic material include induced sputum, bronchial brushings, bronchial washings, percutaneous fine‐needle aspiration (FNA), conventional transbronchial FNA, and endobronchial ultrasound guided FNA . Each technique has characteristic sensitivities and specificities with recent studies suggesting that image guided FNA has the best diagnostic accuracy . Given the importance of these sampling techniques, it is clear that cytopathologists play a central role in the diagnostic evaluation of pulmonary nodules and masses.…”
Section: Proposed Pulmonary Cytology Specimen Terminology and Classifmentioning
confidence: 99%
“…Herth et al [21] also suggested that the use of a 1.15-mm miniforceps increased the diagnostic yield in patients with sarcoidosis (from 36 to 88%) or lymphoma (from 35 to 81%) in a series of 75 patients not suspected of having lung cancer, and, in a noncontrolled case series, the use of a bevel-tip needle forceps was studied [22]. Finally, a recent retrospective study performed by Wang et al [26] comparing conventional EBUS-TBNA to EBUS-MFB in a population with 59% malignant disease showed that diagnostic yield was equal in both groups (94 vs. 95%, respectively). Furthermore, they found that EBUS-TBNA rendered enough material for a diagnosis in 453/476 cases, thus negating the need for the additional MFB biopsy [26].…”
Section: Results Of Pico Questionmentioning
confidence: 99%
“…Finally, a recent retrospective study performed by Wang et al [26] comparing conventional EBUS-TBNA to EBUS-MFB in a population with 59% malignant disease showed that diagnostic yield was equal in both groups (94 vs. 95%, respectively). Furthermore, they found that EBUS-TBNA rendered enough material for a diagnosis in 453/476 cases, thus negating the need for the additional MFB biopsy [26]. In conclusion, the use of a miniforceps does not seem to influence the diagnostic yield in lung cancer but may be useful in patients with a suspected lymphoma or sarcoidosis.…”
Section: Results Of Pico Questionmentioning
confidence: 99%
“…Despite adequate published data on the sensitivity and a specificity of EBUS‐FNA for pulmonary lesions, little data exists as to the malignancy risk associated with commonly utilized diagnostic categories. While no widely accepted diagnostic categorization for pulmonary cytology specimens currently exists, many cytopathologists use a categorization system similar to that published by the Papanicolaou Society of Cytopathology (P.S.C.)…”
Section: Discussionmentioning
confidence: 99%